The genetics of the dog (CABI, 2001)
This multiauthor book comprises comprehensive reviews on all aspects of dog genetics. The first 5 of its 19 chapters deal with systematics, phylogeny, domestication and single-gene traits. The next 7 chapters cover biochemical polymorphism, molecular genetics, immunogenetics, the genetics of disease, genome structure and gene mapping. There follow chapters on the genetics of behaviour, reproduction and development, and the final chapters are devoted to genotype testing, pedigree analysis, quantitative genetics, and the application of dog genetics in the medical and forensic fields. The book is intended for a wide readership, including research workers, lecturers, students, dog breeders and veterinarians. There are appendices on standardized genetic nomenclature for the dog, kennel clubs of the world, international organizations dealing with dogs, and databases on dog breeds and DNA. There is a subject index. The individual chapters of the book have been abstracted separately.